Immersion of nanodiamonds into three-dimensional direct-laser-written waveguides - Gutsche, Jonas; Landowski, Alexander; Von Freymann, Georg; Widera, Artur (Proceedings of SPIE - The International Society for Optical Engineering, 2019)
Waveguide-coupled sensors have several applications such as magnetometry, electrometry or thermometry, harnessing the resolution of nano-sized probes as well as tight light control in macroscopic waveguide networks. We present our approach to incorporate nanodiamonds into direct-laser-written (DLW) three-dimensional photonic structures. The nanodiamonds house ensembles of 103 nitrogen vacancy (NV) centers, acting as probes that can be read-out optically. Guided by the waveguide structure, detection of the optical signal from the nanodiamond does not require direct optical access. In fact, our waveguides combine extended planar sections laid onto the substrate on the one hand with three-dimensional coupling structures on the other hand. The latter effectively rotates the propagation direction of light signals from parallel to the substracte surface within the waveguide network to perpendicular to the substrate at the in- and outputs. This enables simultaneous addressing and imaging of waveguide inputs and outputs through the glass substrate using a single microscope objective. The NV center offers an accurately controllable spin in a solid-state system, serving as a sensitive probe of, e.g., magnetic fields. Additionally these defect centers are photostable and compatible with the DLW process. We show optically detected magnetic resonance spectra together with Rabi oscillations on an effective two-level system in waveguide-embedded nanodiamonds. We compare their performance with free-space emission and complement our experimental studies by numerical simulations. This approach opens the way for on-chip three-dimensional structures for optically integrated spin-based sensing.
CRIS-Team Scopus Importer:2023-03-27
Keywords: Additive Manufacturing; Direct Laser Writing; Nanodiamond; Nitrogen Vacancy